2017
DOI: 10.1039/c7cc06367a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protic additives in Cu-catalysed asymmetric Diels–Alder cycloadditions of doubly activated dienophiles: towards the synthesis of magellanine-type Lycopodium alkaloids

Abstract: The pronounced beneficial effect of a precise amount of protic additive in an enantioselective Cu-catalysed Diels–Alder reaction is reported. This reaction, which employs a cyclic alkylidene β-ketoester as a dienophile, represents one of the first examples of a transformation where these extremely versatile, though highly unstable reaction partners participate effectively in catalytic asymmetric cycloaddition with a functionalised diene. The cycloadduct was used as an intermediate towards the synthesis of mage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Before describing the reported total syntheses of (–)-magellanine, (+)-magellaninone, and (+)-paniculatine ( 1 – 3 ), it is worth highlighting some of the efforts before Overman’s 1993 landmark total synthesis due to their unique strategies in the context of constructing the tetracyclic framework that defines these diquinane alkaloids. Of course, several other synthetic studies have been reported throughout the years between 1993 and the present [ 12 , 13 , 14 ], some of which will be briefly discussed in Section 4 . In lieu of traditional retrosynthetic analyses for these syntheses described in Section 2 , a condensed scheme will be shown to highlight the key transformations utilized in these strategies.…”
Section: Early Synthetic Efforts From 1986–1993mentioning
confidence: 99%
See 1 more Smart Citation
“…Before describing the reported total syntheses of (–)-magellanine, (+)-magellaninone, and (+)-paniculatine ( 1 – 3 ), it is worth highlighting some of the efforts before Overman’s 1993 landmark total synthesis due to their unique strategies in the context of constructing the tetracyclic framework that defines these diquinane alkaloids. Of course, several other synthetic studies have been reported throughout the years between 1993 and the present [ 12 , 13 , 14 ], some of which will be briefly discussed in Section 4 . In lieu of traditional retrosynthetic analyses for these syntheses described in Section 2 , a condensed scheme will be shown to highlight the key transformations utilized in these strategies.…”
Section: Early Synthetic Efforts From 1986–1993mentioning
confidence: 99%
“…With the use of Pd(OAc) 2 (10 mol%) and DavePhos (30 mol%), vinyl triflate 97 was employed to close the C-ring of 98 at a 66% yield. Similar to Meyers, to the best of our knowledge, Sarpong and coworkers have not completed the total synthesis of 1 – 3 ; however, another unique approach was disclosed in 2017 [ 13 ].…”
Section: Other Notable Synthesesmentioning
confidence: 99%
“…We were delighted to find that using the optimal ligand L8 and quenching the reaction at low temperature resulted in silyl-adduct 3a with a small quantity of enone 4a (entry 16). The addition of a protic additive (methanol), performing the reaction in mixed toluene and ethereal solvent, and reducing the temperature further resulted in a modest but significant enhancement in enantioselectivity (entries 17 and 18) . Finally, further reducing the temperature to −55 °C and utilizing cyclopentyl methyl ether (CPME) improved the enantioselectivity of the reaction to 81% ee (entry 19).…”
mentioning
confidence: 99%